Aspects of Sexual Morality of Young People in Gender Perspective - Redžić, Saduša F. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper presents a comparative analysis of data obtained in the sociological study of sexual morality. We used in-depth interviews to collect data for comparison of attitudes between girls and boys on certain aspects of sexual relationships. We asked about: association of sex, love and reproduction, abstinence and promiscuity, initiating intimacy, heterosexual and homosexual relationships, and prostitution. Results indicate a convergence of attitudes of two genders on certain aspects. Their views are sometimes more traditional, than modern or liberal, and sometimes they are classified as transitional. The traditional model still contains attitudes characterized by sexual dimorphism. Modern model loses the importance of gender dimensions. The theoretical and methodological framework consists of theories on the differences between male and female gender roles.
Keywords: sexual relations; sexual morality; the young; in-depth interview